2007
DOI: 10.1038/nn1916
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids mediate analgesia largely via peripheral type 1 cannabinoid receptors in nociceptors

Abstract: Although endocannabinoids constitute one of the first lines of defense against pain, the anatomical locus and the precise receptor mechanisms underlying cannabinergic modulation of pain are uncertain. Clinical exploitation of the system is severely hindered by the cognitive deficits, memory impairment, motor disturbances and psychotropic effects resulting from the central actions of cannabinoids. We deleted the type 1 cannabinoid receptor (CB 1 ) specifically in nociceptive neurons localized in the peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
468
3
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 508 publications
(490 citation statements)
references
References 44 publications
14
468
3
5
Order By: Relevance
“…This was interpreted as indicating antinociceptive effects on a sensory level (Bloom and Dewey, 1978;Chesher et al, 1973), which would further agree with cannabinoid receptors being present in pain circuits from the peripheral sensory nerve endings up to the brain (Manzanares et al, 2006). Endocannabinoids are also involved in endogenous pain inhibition (Walker et al, 2001), as shown in models of chronic inflammatory and neuropathic pain (Agarwal et al, 2007;Bishay et al, 2010). Local injections of cannabinoid receptor agonists reduce pain in various rodent models (Agarwal et al, 2007;Kehl et al, 2003;Lozano-Ondoua et al, 2010).…”
Section: Intrinsic Connections (A Parameter)mentioning
confidence: 78%
See 2 more Smart Citations
“…This was interpreted as indicating antinociceptive effects on a sensory level (Bloom and Dewey, 1978;Chesher et al, 1973), which would further agree with cannabinoid receptors being present in pain circuits from the peripheral sensory nerve endings up to the brain (Manzanares et al, 2006). Endocannabinoids are also involved in endogenous pain inhibition (Walker et al, 2001), as shown in models of chronic inflammatory and neuropathic pain (Agarwal et al, 2007;Bishay et al, 2010). Local injections of cannabinoid receptor agonists reduce pain in various rodent models (Agarwal et al, 2007;Kehl et al, 2003;Lozano-Ondoua et al, 2010).…”
Section: Intrinsic Connections (A Parameter)mentioning
confidence: 78%
“…Endocannabinoids are also involved in endogenous pain inhibition (Walker et al, 2001), as shown in models of chronic inflammatory and neuropathic pain (Agarwal et al, 2007;Bishay et al, 2010). Local injections of cannabinoid receptor agonists reduce pain in various rodent models (Agarwal et al, 2007;Kehl et al, 2003;Lozano-Ondoua et al, 2010). A few human studies also demonstrated a decreased sensitivity and increased tolerance to pain in a THC dose-dependent manner (Cooper et al, 2013;Greenwald and Stitzer, 2000), which is in line with the observation of reduced coupling between thalamus and S2 as the lateral spinothalamic tract is critical for the sensorydiscriminative processing of pain (Maihofner et al, 2006;Price, 2002).…”
Section: Intrinsic Connections (A Parameter)mentioning
confidence: 99%
See 1 more Smart Citation
“…The pain behavior of the SNS-Cre mouse line does not differ from that of wild-type littermates (38), suggesting that the observed hypersensitive phenotype is due to the deletion of NEDD4-2 and not to the expression of Cre recombinase in Na v 1.8-positive nociceptors. The possibility that these differences may also involve non-nociceptive neurons that are potentially subject to Cre recombination cannot be ruled out, as Na v 1.8 expression was recently shown to extend to larger DRG neurons (39).…”
Section: Discussionmentioning
confidence: 93%
“…[16] However, only peripheral CBr1 on nociceptors contribute to antinociception in inflammatory and neuropathic pain models. [1] CBr2 are found on immune cells [31,41] and keratinocytes [15,16]. CBr2 on keratinocytes mediates antinociception via opioid release.…”
Section: Discussionmentioning
confidence: 99%